Penguatan Kapasitas Digital Marketing Pelaku UMKM melalui Pelatihan Canva dan TikTok Shop di Kecamatan Pasar Kemis - Ria Hartati; Akfika Rizky Sabilla; Dewiana Novitasari; Dwi Purwaningrum; Erni Taruli Pebrina; Fatrilia Rasyi Radita; Gazali Gazali; Heni Rusmanto; Lusiana Sari; Maria Novita Olin; Masduki Asbari; Muhammad Nur Kasyfillah Hardjo; Paolinus Hulu; Rachma Nadhila Sudiyono; Rintis Mardika Sunarto; Rony Setiawan; Santa Lusianna Sitorus; Sri Wahyuni Asnaini; Cahya Kartika; Citra Yulianti; Zelda Maulida (Niswantara: Jurnal Pengabdian Kepada Masyarakat, 2026)
Digital transformation has shifted micro, small, and medium enterprises (MSMEs) from conventional marketing toward digital-based promotional strategies. However, many MSME owners still experience limitations in developing brand identity, producing attractive promotional content, and utilizing social media as an effective marketing channel. This community engagement program aimed to strengthen the digital marketing capacity of MSMEs through Canva and TikTok Shop training in Pasar Kemis District, Tangerang Regency. The program adopted a Participatory Action Approach consisting of needs assessment, program planning, training implementation, hands-on practice, mentoring, evaluation, and sustainability planning. Training materials included promotional content design using Canva, branding strategies, TikTok algorithms, TikTok Shop optimization, and live commerce practices. The implementation demonstrated high participant engagement, improved understanding of digital marketing concepts, and enhanced participants' ability to create attractive promotional materials. Beyond improving individual competencies, the program also strengthened collaboration between the university and the local MSME community in supporting digital transformation. The findings indicate that practice-based training combined with continuous mentoring is an effective strategy to accelerate digital technology adoption among MSMEs. Sustainable mentoring programs are therefore recommended to maximize business competitiveness and long-term enterprise sustainability.